A high-temperature and high-pressure deformation assembly suitable for a large-cavity press and its application
By designing a deformation assembly based on diamond plugs, using bevel polycrystalline diamond column plugs and other material components to provide pressure, shear force and heating, the problem of harsh temperature and pressure conditions for fullerene C60 to diamond in the prior art is solved, and the effect of synthesizing diamond under relatively mild conditions is achieved.
Patent Information
- Application Number
- CN202310091404.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-02-07
AI Technical Summary
The prior art is difficult to achieve the transformation of fullerene C60 to diamond under relatively mild temperature and pressure conditions, and the high temperature and high pressure conditions are harsh.
A deformation assembly based on diamond plugs was designed, including an oblique polycrystalline diamond column plug provided between magnesium oxide tubes. Combining materials such as aluminum oxide, zirconium oxide column and rhenium metal tubes, a sample chamber is formed and pressure, shear force and heating are provided to achieve structural phase transformation of C60.
The temperature and pressure conditions for the transition of fullerene C60 to diamond were successfully reduced, and the possibility of synthesizing diamond materials under relatively mild conditions was realized.
Smart Images

Figure CN116084004B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high temperature and high pressure for large cavity presses, and in particular relates to a deformation assembly based on a diamond plug suitable for a high temperature and high pressure large cavity press and an application thereof. Background Art
[0002] Large cavity presses have a large sample synthesis cavity of millimeters to centimeters, which can accurately control temperature and pressure and perform in-situ physical property measurements. They are widely used in natural science and industry. In particular, diamonds synthesized using large cavity presses have been widely used in industry.
[0003] In existing commercial non-deformation large cavity presses, the high-pressure assembly usually provides a radial quasi-hydrostatic stress loading environment in the sample chamber. In non-deformation large cavity presses, the design and development of a shear deformation assembly that is generally suitable for commercial non-deformation large cavity presses can effectively carry out high-pressure deformation experiments and study the physical and chemical properties of materials under non-hydrostatic pressure conditions.
[0004] At present, people have designed and developed bevel Al 2 O 3 Assemble the body and conduct high-pressure deformation experiments to simulate the evolution of various slip systems of geological minerals under high temperature and high pressure. 2 O 3 The hardness of the assembly is relatively low, about 15-19GPa, which limits its shear stress loading on harder materials or even superhard materials. Finding and developing high-hardness shear deformation assembly materials has become the technical key to deformation assembly. As we all know, diamond is the hardest material in nature. The deformation assembly designed and developed based on diamond material can effectively break through the shear stress loading limit of the original material, making it possible to effectively load shear stress in high temperature and high pressure experiments.
[0005] High pressure deformation can effectively promote the transformation of carbon materials into diamond. 60 As an allotrope of carbon, it is a spherical structure similar to a soccer ball, consisting of 12 carbon five-membered rings and 20 carbon six-membered rings. 48 atoms have quasi-tetrahedral coordination, which is quite close to diamond in space. Under high temperature and high pressure quasi-static water conditions, 15GPa, 1500-1600℃, C 60 The temperature and pressure conditions required to begin to transform into diamond are relatively harsh, and there is an urgent need to develop high-pressure deformation technology to lower the temperature and pressure conditions for its synthesis. Summary of the invention
[0006] The purpose of the present invention is to provide a high temperature and high pressure deformation assembly suitable for a large cavity press and its application, which can effectively reduce the temperature and pressure conditions for the transformation of fullerene to diamond by applying shear force to the sample under high temperature and high pressure.
[0007] The present invention provides a deformation assembly based on a diamond plug suitable for a high-temperature, high-pressure, large-cavity press, comprising: a magnesium oxide tube 7, a first beveled polycrystalline diamond column plug 9-1 and a second beveled polycrystalline diamond column plug 9-2 arranged at intervals in the magnesium oxide tube 7; the first beveled polycrystalline diamond column plug 9-1 comprises a first plane and a first inclined elliptical surface opposite to the first plane; the second beveled polycrystalline diamond column plug 9-2 comprises a second plane and a second inclined elliptical surface opposite to the second plane; the first plane is flush with an opening at one end of the magnesium oxide tube 7, and the second plane is flush with an opening at the other end of the magnesium oxide tube 7;
[0008] Inside the magnesium oxide tube 7, a sample chamber 8 is formed between the first inclined elliptical surface and the second inclined elliptical surface;
[0009] The first alumina column 5-1 and the first zirconia column 6-1 contacting each other are sequentially arranged outside the opening of one end of the magnesium oxide tube 7; the second alumina column 5-2 and the second zirconia column 6-2 contacting each other are sequentially arranged outside the opening of the other end of the magnesium oxide tube 7;
[0010] A rhenium metal tube 4 sleeved on the outer circumference of the first zirconia column 6-1, the first alumina column 5-1, the magnesium oxide tube 7, the second alumina column 5-2 and the second zirconia column 6-2;
[0011] A zirconia tube 2 sleeved on the outer circumference of the rhenium metal tube 4;
[0012] The outer peripheral surface of the zirconium oxide tube 2 and the magnesium oxide octahedron 1 with openings at both ends are encapsulated.
[0013] Preferably, the diameters of the first beveled polycrystalline diamond column plug 9 - 1 and the second beveled polycrystalline diamond column plug 9 - 2 are both 0.8 mm.
[0014] Preferably, the inclination angle of the first inclined elliptical surface is 45°; the inclination angle of the second inclined elliptical surface is 45°.
[0015] Preferably, it also includes: a thermocouple 3 fixedly connected to the rhenium metal tube 4 .
[0016] The present invention provides the application of the deformation assembly described in the above technical solution as an assembly of a high-temperature and high-pressure large-cavity press.
[0017] The present invention provides a method for preparing diamond material, which is prepared by using the deformation assembly described in the above technical solution;
[0018] The following steps are involved:
[0019] Fullerene C 60The material is loaded into the sample chamber of the deformation assembly described in the above technical solution;
[0020] The fullerene C loaded into the sample chamber 60 The material undergoes a structural phase change under the heat preservation and pressure holding conditions to obtain a diamond material; the heat preservation and pressure holding conditions are: the pressure of the sample chamber is ≥15GPa, and the temperature of the sample chamber is ≥1000°C and <1200°C.
[0021] Preferably, the fullerene C 60 Before the material is loaded into the sample chamber, the method further comprises: placing the fullerene C 60 The material is subjected to vacuum annealing treatment; the temperature of the vacuum annealing treatment is 150-200°C, the insulation time of the vacuum annealing treatment is 2-3h; the heating rate from room temperature to the temperature of the vacuum annealing treatment is 5-10°C.
[0022] Preferably, obtaining a phase change material after the structural phase change further comprises: quenching the phase change material to obtain the diamond material.
[0023] Preferably, the heat preservation and pressure preservation time is 0.5 to 1 hour.
[0024] Preferably, the fullerene C 60 The purity of the material is ≥99.9%.
[0025] The present invention provides a deformation assembly based on a diamond plug suitable for a high-temperature, high-pressure, large-cavity press, comprising: a magnesium oxide tube 7, a first beveled polycrystalline diamond column plug 9-1 and a second beveled polycrystalline diamond column plug 9-2 arranged at intervals in the magnesium oxide tube 7; the first beveled polycrystalline diamond column plug 9-1 comprises a first plane and a first inclined elliptical surface opposite to the first plane; the second beveled polycrystalline diamond column plug 9-2 comprises a second plane and a second inclined elliptical surface opposite to the second plane; the first plane is flush with an opening at one end of the magnesium oxide tube 7, and the second plane is flush with an opening at the other end of the magnesium oxide tube 7; Inside the magnesium oxide tube 7, a sample chamber 8 is formed between the first inclined elliptical surface and the second inclined elliptical surface; the first aluminum oxide column 5-1 and the first zirconium oxide column 6-1 contacting each other are arranged in sequence on the outside of the opening at one end of the magnesium oxide tube 7; the second aluminum oxide column 5-2 and the second zirconium oxide column 6-2 contacting each other are arranged in sequence on the outside of the opening at the other end of the magnesium oxide tube 7; a rhenium metal tube 4 is sleeved on the outer peripheral surfaces of the first zirconium oxide column 6-1, the first aluminum oxide column 5-1, the magnesium oxide tube 7, the second aluminum oxide column 5-2 and the second zirconium oxide column 6-2; a zirconium oxide tube 2 is sleeved on the outer peripheral surface of the rhenium metal tube 4; and a magnesium oxide octahedron 1 encapsulating the outer peripheral surface of the zirconium oxide tube 2 and the openings at both ends. The deformation assembly provided by the present invention forms a sample chamber between the inclined elliptical surface of the first beveled polycrystalline diamond column plug 9-1 and the inclined elliptical surface of the second beveled polycrystalline diamond column plug 9-2; the first beveled polycrystalline diamond column plug 9-1 and the second beveled polycrystalline diamond column plug 9-2 simultaneously apply pressure and shear force to the sample in the sample chamber, thereby achieving structural phase change of the sample under relatively mild temperature and pressure conditions; at the same time, the present invention adopts the first zirconium oxide column 6-1, the first aluminum oxide column 5-1, and the second The alumina column 5-2 and the second zirconia column 6-2 transmit pressure to the first beveled polycrystalline diamond column plug 9-1 and the second beveled polycrystalline diamond column plug 9-2, the rhenium metal tube 4 is used to heat the sample chamber, and the zirconia tube 2 is used to reinforce and keep warm; finally, the magnesium oxide octahedron 1 is used for packaging, so that the deformation assembly can have a stable structure and perform stable pressurization and heating operations on the sample in the sample chamber, and at the same time provide shear force to the sample in the sample chamber, so as to achieve structural phase change of the sample under relatively mild temperature and pressure conditions.
[0026] The preparation method provided by the present invention adopts the deformation assembly described in the above technical solution to C 60 While the material is being treated with high temperature and high pressure, 60 The material provides shear force, achieving C 60 The material undergoes a structural phase change under relatively mild temperature and pressure conditions to obtain diamond material, which greatly reduces the temperature and pressure conditions for synthetic diamond. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a curve diagram of the actual pressure in the cavity changing with the oil pressure in Example 1;
[0028] Figure 2 This is a curve diagram of the actual pressure in the cavity changing with the oil pressure in comparative example 1;
[0029] Figure 3 is an optical photograph of the bulk diamond sample synthesized in Example 1;
[0030] Figure 4 is an optical photograph of the bulk diamond sample synthesized in Comparative Example 1;
[0031] Figure 5 XRD spectra of the bulk diamond samples synthesized in Example 1 and Comparative Example 1;
[0032] Figure 6 A schematic diagram of the structure of a deformable assembly provided by an embodiment of the present invention;
[0033] Figure 6 In the figure, 1 is a magnesium oxide octahedron, 2 is a zirconium oxide tube, 3 is a thermocouple, 4 is a rhenium metal tube, 5-1 is a first alumina column, 5-2 is a second alumina column, 6-1 is a first zirconium oxide column, 6-2 is a second zirconium oxide column, 7 is a magnesium oxide tube, 8 is a sample chamber, 9-1 is a first beveled polycrystalline diamond column plug, and 9-2 is a second beveled polycrystalline diamond column plug;
[0034] Figure 7 A physical diagram of the components used in the deformable assembly provided in the embodiment of the present invention;
[0035] Figure 8 A schematic diagram of the structure of a non-deformable conventional assembly provided as a comparative example of the present invention;
[0036] Figure 8 In the figure, 10 is a magnesium oxide octahedron, 11 is a first magnesium oxide tube, 12 is a second magnesium oxide tube, 13 is a magnesium oxide column, 14 is a zirconium oxide column, 15 is magnesium oxide particles, 16 is a four-hole aluminum oxide column, 17 is a thermocouple, 18 is an aluminum oxide sheet, 19 is a sample chamber; 20 is a rhenium metal heater; 21 is a lanthanum chromate tube;
[0037] Fig. 9 A physical diagram of the components used in the non-deformed conventional assembly provided as a comparative example of the present invention. DETAILED DESCRIPTION
[0038] The present invention provides a deformation assembly based on a diamond plug suitable for a high-temperature, high-pressure, large-cavity press, comprising: a magnesium oxide tube 7, a first beveled polycrystalline diamond column plug 9-1 and a second beveled polycrystalline diamond column plug 9-2 arranged at intervals in the magnesium oxide tube 7; the first beveled polycrystalline diamond column plug 9-1 comprises a first plane and a first inclined elliptical surface opposite to the first plane; the second beveled polycrystalline diamond column plug 9-2 comprises a second plane and a second inclined elliptical surface opposite to the second plane; the first plane is flush with an opening at one end of the magnesium oxide tube 7, and the second plane is flush with an opening at the other end of the magnesium oxide tube 7;
[0039] Inside the magnesium oxide tube 7, a sample chamber 8 is formed between the first inclined elliptical surface and the second inclined elliptical surface;
[0040] The first alumina column 5-1 and the first zirconia column 6-1 contacting each other are sequentially arranged outside the opening of one end of the magnesium oxide tube 7; the second alumina column 5-2 and the second zirconia column 6-2 contacting each other are sequentially arranged outside the opening of the other end of the magnesium oxide tube 7;
[0041] A rhenium metal tube 4 sleeved on the outer circumference of the first zirconia column 6-1, the first alumina column 5-1, the magnesium oxide tube 7, the second alumina column 5-2 and the second zirconia column 6-2;
[0042] A zirconia tube 2 sleeved on the outer circumference of the rhenium metal tube 4;
[0043] The outer peripheral surface of the zirconium oxide tube 2 and the magnesium oxide octahedron 1 with openings at both ends are encapsulated.
[0044] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0045] The deformable assembly provided by the present invention includes a magnesium oxide tube 7 .
[0046] In the present invention, the magnesium oxide tube 7 is used to form a sample chamber to contain the sample.
[0047] In the deformation assembly provided by the present invention, a first beveled polycrystalline diamond column plug 9-1 and a second beveled polycrystalline diamond column plug 9-2 are arranged at intervals in the magnesium oxide tube 7; the first beveled polycrystalline diamond column plug 9-1 includes a first plane and a first inclined elliptical surface opposite to the first plane; the second beveled polycrystalline diamond column plug 9-2 includes a second plane and a second inclined elliptical surface opposite to the second plane; the first plane is flush with one end opening of the magnesium oxide tube 7, and the second plane is flush with the other end opening of the magnesium oxide tube 7.
[0048] In the deformable assembly provided by the present invention, a sample chamber 8 is formed inside the magnesium oxide tube 7 between the first inclined elliptical surface and the second inclined elliptical surface.
[0049] In the present invention, the diameter of the first beveled polycrystalline diamond column plug 9-1 is preferably 0.8 mm.
[0050] In the present invention, the diameter of the second beveled polycrystalline diamond column plug 9-2 is preferably 0.8 mm.
[0051] In the present invention, the inclination angle of the first inclined elliptical surface is preferably 45°.
[0052] In the present invention, the long axis length of the first inclined elliptical surface is 1.13 mm, the short axis length is 0.8 mm, and the area of the first inclined elliptical surface is 0.710 mm. 2 .
[0053] In the present invention, the inclination angle of the second inclined elliptical surface is preferably 45°.
[0054] In the present invention, the major axis length of the second inclined elliptical surface is 1.13 mm, the minor axis length is 0.8 mm, and the area of the second inclined elliptical surface is 0.710 mm. 2 .
[0055] In the present invention, the preparation method of the first beveled polycrystalline diamond column plug 9-1 and the second beveled polycrystalline diamond column plug 9-2 preferably comprises the following steps:
[0056] The polycrystalline diamond column is cut by laser to obtain the first beveled polycrystalline diamond column plug 9-1 and the second beveled polycrystalline diamond column plug 9-2.
[0057] In the present invention, the height of the polycrystalline diamond column is preferably 1 mm, and the diameter is preferably 0.8 mm.
[0058] In the present invention, the laser cutting is preferably performed by using a laser with an excitation wavelength of 532 nm; the laser cutting is preferably performed in a laser cutting machine. The present invention uses a laser to cut the polycrystalline diamond column into two sections at an angle of 45° from the middle height of the column cross section, and the inclined surface is elliptical, to obtain a first beveled polycrystalline diamond column plug 9-1 and a second beveled polycrystalline diamond column plug 9-2.
[0059] In the present invention, the first beveled polycrystalline diamond column plug 9-1 and the second beveled polycrystalline diamond column plug 9-2 are used to form a sample chamber 8 inside the magnesium oxide tube 7. In the present invention, the two inner surfaces of the sample chamber 8 are respectively the first inclined elliptical surface and the second inclined elliptical surface; the first inclined elliptical surface and the second inclined elliptical surface can provide pressure and shear force to the sample in the sample chamber at the same time, so that the sample in the sample chamber is subjected to the high pressure and the shear force at the same time.
[0060] In the deformation assembly provided by the present invention, a first alumina column 5-1 and a first zirconia column 6-1 contacting each other are sequentially arranged outside the opening at one end of the magnesium oxide tube 7; a second alumina column 5-2 and a second zirconia column 6-2 contacting each other are sequentially arranged outside the opening at the other end of the magnesium oxide tube 7.
[0061] In the present invention, one end of the first alumina column 5-1 contacts the plane of the first beveled polycrystalline diamond column plug 9-1, and the other end of the first alumina column 5-1 contacts one end of the first alumina column 6-1.
[0062] In the present invention, one end of the second alumina column 5-2 contacts the plane of the first beveled polycrystalline diamond column plug 9-1, and the other end of the second alumina column 5-2 contacts one end of the second alumina column 6-2.
[0063] In the present invention, the first zirconia column 6-1, the first alumina column 5-1, the second alumina column 5-2 and the second zirconia column 6-2 are used to transmit pressure to the first beveled polycrystalline diamond column plug 9-1 and the second beveled polycrystalline diamond column plug 9-2.
[0064] The deformation assembly provided by the present invention includes a rhenium metal tube 4 sleeved on the outer peripheral surfaces of the first zirconia column 6-1, the first alumina column 5-1, the magnesium oxide tube 7, the second alumina column 5-2 and the second zirconia column 6-2.
[0065] In the present invention, the rhenium metal tube 4 is used to heat the sample chamber 8 .
[0066] In the present invention, the inner diameter of the rhenium metal tube 4 is preferably 1.6 mm.
[0067] The deformation assembly provided by the present invention preferably further includes a thermocouple 3 fixedly connected to the rhenium metal tube 4 .
[0068] The present invention uses the thermocouple to monitor the temperature change of the rhenium metal tube 4 .
[0069] The deformation assembly provided by the present invention comprises a zirconia tube 2 sleeved on the outer peripheral surface of the rhenium metal tube 4 .
[0070] In the present invention, the function of the zirconia tube 2 is to keep warm and prevent heat loss.
[0071] The deformable assembly provided by the present invention comprises an outer peripheral surface encapsulating the zirconium oxide tube 2 and a magnesium oxide octahedron 1 with openings at both ends.
[0072] In the present invention, the magnesium oxide octahedron 1 is used to encapsulate the outer peripheral surface and the openings at both ends of the zirconium oxide tube 2 to protect the deformed assembly.
[0073] In the present invention, the surfaces of the magnesium oxide octahedron 1 and the zirconium oxide tube 2 are both provided with small holes through which the thermocouple 3 passes.
[0074] The present invention provides the application of the deformation assembly described in the above technical solution as an assembly of a high-temperature, high-pressure, large-cavity press.
[0075] The present invention provides a method for preparing diamond material, which is prepared by using the deformation assembly described in the above technical solution;
[0076] The following steps are involved:
[0077] Fullerene C 60 The material is loaded into the sample chamber of the deformation assembly described in the above technical solution;
[0078] The fullerene C loaded into the sample chamber 60 The material undergoes a structural phase change under the conditions of heat preservation and pressure preservation to obtain a diamond material; the heat preservation and pressure preservation conditions are: the pressure of the sample chamber is ≥15GPa, and the temperature of the sample chamber is ≥1000°C and <1200°C.
[0079] The present invention will C 60 The material is loaded into the sample chamber of the deformation assembly described in the above technical solution.
[0080] In the present invention, the fullerene C 60 The purity of the material is preferably ≥ 99.9%.
[0081] The present invention preferably assembles the deformation assembly into a high-temperature, high-pressure, large-cavity press to cause the structural phase change. In the present invention, the high-temperature, high-pressure, large-cavity press is preferably a Walker-type multi-faceted anvil high-temperature, high-pressure, large-cavity press.
[0082] In the present invention, the fullerene C 60 Before the material is loaded into the sample chamber, the present invention preferably further comprises: placing the fullerene C 60The material is subjected to vacuum annealing treatment; the temperature of the vacuum annealing treatment is preferably 150-200°C, more preferably 180-200°C; the holding time of the vacuum annealing treatment is preferably 2-3h, more preferably 2h; the heating rate from room temperature to the temperature of the vacuum annealing treatment is preferably 5-10°C, more preferably 5°C.
[0083] The present invention loads the fullerene C in the sample chamber. 60 The material undergoes a structural phase change under heat preservation and pressure holding conditions to obtain a diamond material; the heat preservation and pressure holding conditions are: the pressure of the sample chamber is ≥15GPa, preferably 15GPa, and the temperature of the sample chamber is ≥1000°C and <1200°C, preferably 1000°C.
[0084] In the present invention, the method for obtaining the temperature and pressure conditions of the sample chamber preferably includes the following steps: increasing the pressure of the sample chamber from 1 atmosphere to the required pressure; increasing the temperature of the sample chamber from room temperature; and obtaining the required temperature. In the present invention, the time for the pressure increase is preferably 11 hours. The present invention has no special requirements for the time for the temperature increase.
[0085] In the present invention, the heat preservation and pressure preservation time of the structural phase change is 0.5 to 1 hour, more preferably 1 hour.
[0086] In the present invention, after the structural phase change, a phase change material is obtained, and the present invention preferably further comprises: quenching the phase change material to obtain the diamond material. In the present invention, the end temperature of the quenching is preferably room temperature. In the present invention, after the quenching, the present invention preferably unloads the pressure of the sample chamber to normal pressure and takes out the diamond material product.
[0087] In the present invention, the diamond material product is a millimeter-scale product.
[0088] The present invention is based on the application of a deformation assembly of a diamond plug under temperature and pressure conditions for fullerene to diamond phase transition. The present invention uses a deformation assembly combined with a Walker-type multi-faceted anvil high-temperature and high-pressure large-cavity press unit. The deformation assembly described in the above technical solution is a millimeter-level cavity high-pressure shear deformation device. The present invention successfully synthesizes millimeter-level diamond materials under relatively low temperature and pressure using the deformation assembly described in the above technical solution.
[0089] In order to further illustrate the present invention, the technical solution provided by the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0090] Example 1
[0091] A laser marking machine with an excitation wavelength of 532 nm is used to cut a polycrystalline diamond column with a height of 1 mm and a diameter of 0.8 mm into two sections from the middle, with the cutting angle being 45° to the cylindrical cross section; a first beveled polycrystalline diamond column plug 9-1 and a second beveled polycrystalline diamond column plug 9-2 are obtained;
[0092] Assemble the magnesium oxide tube 7, the first beveled polycrystalline diamond column plug 9-1, the second beveled polycrystalline diamond column plug 9-2, the first zirconium oxide column 6-1, the first aluminum oxide column 5-1, the second aluminum oxide column 5-2 and the second zirconium oxide column 6-2, the rhenium metal tube 4, the zirconium oxide tube 2, the magnesium oxide octahedron 1 and the thermocouple 3 to obtain Figure 6 The structural deformation assembly shown in FIG. 1 ; the actual pictures of the various components are as follows Figure 7 As shown;
[0093] in Figure 6 In the figure, 1 is a magnesium oxide octahedron, 2 is a zirconium oxide tube, 3 is a thermocouple, 4 is a rhenium metal tube, 5-1 is a first alumina column, 5-2 is a second alumina column, 6-1 is a first zirconium oxide column, 6-2 is a second zirconium oxide column, 7 is a magnesium oxide tube, 8 is a sample chamber, 9-1 is a first beveled polycrystalline diamond column plug, and 9-2 is a second beveled polycrystalline diamond column plug;
[0094] Take 2 mg of 99.9% pure C 60 , annealing treatment was performed at 200°C for 2 hours at a heating rate of 5°C per minute in a vacuum atmosphere in a vacuum muffle furnace, and then automatically cooled to room temperature;
[0095] This embodiment uses a Walker type MaxVoggenzeitez, LPR1000-400 / 50 six eight-mode high pressure device; the first beveled polycrystalline diamond column plug 9-1 and the second beveled polycrystalline diamond column plug 9-2 and the heat-treated high purity C 60 The powder is placed in the magnesium oxide tube 7; the assembly is placed in a Walker type high pressure device, according to the pressure calibration curve (such as Figure 1 ), pressurized to 15GPa (330bar) after 11h, heated to 1000℃ with a rhenium tube, kept warm for 1h, then quenched to room temperature, depressurized to normal pressure after 11h, and the product was taken out.
[0096] The product prepared in Example 1 was placed in an acetone solution for ultrasonic treatment, and the sample was polished with a diamond polishing disk to facilitate characterization testing;
[0097] The carbon samples intercepted at atmospheric pressure were tested by optical photographs (such as Figure 3 ), the sample was found to be grayish black and opaque. Using a copper target (0.15418 nm) as the light source, the XRD diffraction of the sample was tested (e.g. Figure 5), obvious crystal diffraction peaks were collected at 19.8°, 32.7° and 38.5°, corresponding to the (111), (200) and (311) planes of the diamond phase, and the background signal of the diffraction pattern was flat, without other impurity peaks, indicating that relatively pure diamond material was successfully synthesized.
[0098] Comparative Example 1
[0099] Take 4 mg of 99.9% pure C 60 , annealing treatment was performed at 200°C for 2 hours at a heating rate of 5°C per minute in a vacuum atmosphere in a vacuum muffle furnace, and then automatically cooled to room temperature.
[0100] This embodiment uses the same high pressure device as that of embodiment 1; the high purity C 60 The powder is placed in a high pressure assembly and assembled as Figure 8 , Figure 8 10 is a magnesium oxide octahedron, 11 is a first magnesium oxide tube, 12 is a second magnesium oxide tube, 13 is a magnesium oxide column, 14 is a zirconium oxide column, 15 is a magnesium oxide particle, 16 is a four-hole aluminum oxide column, 17 is a thermocouple, 18 is an aluminum oxide sheet, 19 is a sample chamber; 20 is a rhenium metal heater; 21 is a lanthanum chromate tube; the actual pictures of the components are as shown in FIG. Fig. 9 As shown;
[0101] Place the assembly into a Walker-type high pressure device and adjust the pressure according to the pressure calibration curve (such as Figure 2 ), pressurized to 15GPa (210bar) after 8h, heated to 1000℃ with a rhenium tube, kept warm for 1h, then quenched to room temperature, and depressurized to normal pressure after 8h. Take out the product.
[0102] The product of this comparative example was placed in an acetone solution for ultrasonic treatment, and the sample was polished with a diamond polishing disk to facilitate characterization testing.
[0103] The carbon samples intercepted at atmospheric pressure were tested and the optical photographs (such as Figure 4 ), the sample was found to be bright black and opaque. Using a copper target (0.15418 nm) as the light source, the XRD diffraction of the sample was tested (e.g. Figure 5 ), obvious crystal diffraction peaks were collected at 30.1° (d = 2.97) and 41.6° (d = 2.16), which is consistent with the Russian scientist NR Serebryaya's C 60 The product obtained after high temperature and high pressure treatment at 12 GPa and 1500 ° C has a similar structure. It is believed that the two-halo diffraction pattern of the disordered phase corresponds to the sp 3 The bond-crosslinked corrugated graphene has a layered structure with unequal interlayer spacing.
[0104] Based on the comparative analysis of the above experimental results, compared with the non-shear high-pressure experiment, in Comparative Example 1 of the present invention, sp with unequal interlayer spacing was synthesized under high temperature and high pressure conditions of 15 GPa and 1000 °C. 3 The present invention uses a diamond material deformation assembly designed by the present invention to synthesize a high purity diamond under the same temperature and pressure conditions (Example 1). Therefore, through experimental comparison, the present invention uses a high temperature and high pressure experimental technology based on a diamond material deformation assembly to promote the synthesis of fullerene C 60 The phase transition to diamond reduces the fullerene C 60 The temperature and pressure conditions for synthetic diamonds have enabled the preparation of diamond bulk materials under relatively mild conditions. It is expected that this deformation assembly can be used to prepare diamond bulk materials with excellent performance under even lower temperature and pressure conditions.
[0105] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a diamond material, characterized in that: A deformation assembly based on a diamond plug and suitable for a high-temperature, high-pressure, large-cavity press is prepared. The deformation assembly based on a diamond plug and suitable for a high-temperature, high-pressure, large-cavity press comprises: a magnesium oxide tube (7), a first beveled polycrystalline diamond column plug (9-1) and a second beveled polycrystalline diamond column plug (9-2) arranged at intervals in the magnesium oxide tube (7); the first beveled polycrystalline diamond column plug (9-1) comprises a first plane and a first inclined elliptical surface opposite to the first plane; the second beveled polycrystalline diamond column plug (9-2) comprises a second plane and a second inclined elliptical surface opposite to the second plane; the first plane is flush with an opening at one end of the magnesium oxide tube (7), and the second plane is flush with an opening at the other end of the magnesium oxide tube (7); Inside the magnesium oxide tube (7), a sample chamber (8) is formed between the first inclined elliptical surface and the second inclined elliptical surface; A first alumina column (5-1) and a first zirconia column (6-1) in contact with each other are sequentially arranged outside the opening at one end of the magnesium oxide tube (7); a second alumina column (5-2) and a second zirconia column (6-2) in contact with each other are sequentially arranged outside the opening at the other end of the magnesium oxide tube (7); A rhenium metal tube (4) sleeved on the outer circumference of the first zirconium oxide column (6-1), the first aluminum oxide column (5-1), the magnesium oxide tube (7), the second aluminum oxide column (5-2) and the second zirconium oxide column (6-2); a zirconium oxide tube (2) sleeved on the outer peripheral surface of the rhenium metal tube (4); A magnesium oxide octahedron (1) encapsulating the outer peripheral surface of the zirconium oxide tube (2) and the two ends of which are open; The following steps are involved: Fullerene C 60 The material is loaded into the sample chamber of the deformation assembly based on the diamond plug suitable for high temperature and high pressure large cavity press; the fullerene C 60 Before the material is loaded into the sample chamber, the method further comprises: placing the fullerene C 60 The material is subjected to vacuum annealing treatment; the temperature of the vacuum annealing treatment is 150-200°C; The fullerene C loaded into the sample chamber 60 The material undergoes a structural phase change under the heat preservation and pressure holding conditions to obtain a diamond material; the heat preservation and pressure holding conditions are: the pressure of the sample chamber is 15 GPa, and the temperature of the sample chamber is ≥1000°C and <1200°C.
2. The preparation method according to claim 1, characterized in that: The diameters of the first beveled polycrystalline diamond column plug (9-1) and the second beveled polycrystalline diamond column plug (9-2) are both 0.8 mm.
3. According to the preparation method according to claim 2, it is characterized in that: The inclination angle of the first inclined elliptical surface is 45°; the inclination angle of the second inclined elliptical surface is 45°.
4. The preparation method according to claim 1, characterized in that: The diamond plug-based deformation assembly suitable for a high-temperature, high-pressure, large-cavity press also includes a thermocouple (3) fixedly connected to the rhenium metal tube (4).
5. The preparation method according to claim 1, characterized in that: The holding time of the vacuum annealing treatment is 2 to 3 hours; the heating rate from room temperature to the temperature of the vacuum annealing treatment is 5 to 10°C.
6. The preparation method according to claim 1, characterized in that: The phase change material is obtained after the structural phase change, and the method further comprises: quenching the phase change material to obtain the diamond material.
7. The preparation method according to claim 1, characterized in that: The time of heat preservation and pressure preservation is 0.5 to 1 hour.
8. The preparation method according to claim 1 or 5, characterized in that: The fullerene C 60 The purity of the material is ≥99.9%.
Citation Information
Patent Citations
High-pressure strain device and preparation method of high-pressure reinforced metal
CN113337787A